Teologi Islam dan Pemberdayaan: Spirit Filantropi Qur’an Berbasis Manajemen Keuangan - Abdul Malik; Achmad Abubakar; Muhsin Mahfudz (STAI Darul Kamal NW Kembang Kerang, 2026)
Islam is a prophetic religion revealed to promote social transformation and address fundamental social problems in human life. One of its essential roles is offering solutions to socio-economic inequality through philanthropic instruments. Zakat, as a compulsory religious obligation, serves not only as an act of worship but also as a strategic mechanism for economic development and social welfare. This article formulates two main research questions: first, what social spirit is embedded in Qur’anic verses related to zakat-based philanthropy; and second, how this social spirit can be developed through effective financial management. Employing a social interpretation approach as the analytical framework, this study identifies several key findings. Thematically, Qur’anic verses on zakat and philanthropy emphasize significant concepts such as yunfiqu amwālahum (QS. al-Baqarah: 261), tukhfūhā al-fuqarā’ (QS. al-Baqarah: 271), and fī amwālihim ḥaqqun (QS. al-Dhāriyāt: 19). These verses convey core social messages of the Qur’an, including social concern, ethical conduct, and socio-moral responsibility toward vulnerable groups. Moreover, zakat, infaq, and alms are directed toward productive and sustainable activities to foster economic independence among the poor. This objective is supported through strengthened financial management, encompassing financial literacy for beneficiaries, empowerment-based zakat governance, and continuous assistance to enhance economic resilience and adaptability.